2022
DOI: 10.1002/ajmg.a.62900
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial variability in six family members with ERF‐related craniosynostosis syndrome type 4

Abstract: ERF-related craniosynostosis syndrome type 4 (CRS4, OMIM #600775) is a rare autosomal dominant malformation syndrome, caused by pathogenic variants in the ERF gene and characterized by craniosynostosis, developmental delay, and dysmorphic features such as hypertelorism, exophthalmos, depressed nasal bridge, and retrognathia. So far, there are mostly individual reports and only a few descriptions of families with more than two affected patients, allowing statements about the penetrance of a certain variant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Yamada et al (2021) reported a patient with a Noonan syndrome-like phenotype associated with an ERF truncating variant. Other previous reports of ERF-related disorders did not describe a Noonan syndrome-like phenotype, but in some patients, overlapping phenotypes were noted retrospectively (Chaudhry et al, 2015;Glass et al, 2019;Körberg et al, 2020;Moddemann et al, 2022;Twigg et al, 2013;Yamada et al, 2021). A summary of the reported characteristics of patients with ERF variants is presented in Table 1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Yamada et al (2021) reported a patient with a Noonan syndrome-like phenotype associated with an ERF truncating variant. Other previous reports of ERF-related disorders did not describe a Noonan syndrome-like phenotype, but in some patients, overlapping phenotypes were noted retrospectively (Chaudhry et al, 2015;Glass et al, 2019;Körberg et al, 2020;Moddemann et al, 2022;Twigg et al, 2013;Yamada et al, 2021). A summary of the reported characteristics of patients with ERF variants is presented in Table 1.…”
Section: Discussionmentioning
confidence: 93%
“…Yumi Enomoto and Takuya Naruto performed the bioinformatics experiments and contributed to the genetics experiments. Yasuhiro Hirano and Yukiko Kuroda recruited T A B L E 1 Summary of the clinical data for reported patients with pathogenic ERF variants (Chaudhry et al, 2015;Glass et al, 2019;Körberg et al, 2020;Moddemann et al, 2022;Twigg et al, 2013;Yamada et al, 2021).…”
Section: Author Contributionsmentioning
confidence: 99%